2017
DOI: 10.18632/oncotarget.19038
|View full text |Cite
|
Sign up to set email alerts
|

Time to local recurrence as a predictor of survival in unrecetable gastric cancer patients after radical gastrectomy

Abstract: Local recurrence is common after radical surgery. However, the factors that contribute to survival after local recurrence remain unclear. In this retrospective study we analyzed the relationship between time to recurrence and survival after recurrence in 74 patients with locally recurrent gastric cancer. All patients received palliative radiotherapy with or without chemotherapy. The patients were divided into two groups according to the time between gastrectomy and local recurrence: early local recurrence (ELR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…Thus, tumor local relapse remains one of the major problems in managing STS, and can be defined as early or late recurrence. In breast adenocarcinoma, renal cell carcinoma, and gastric cancer, it was previously reported that patients with late recurrence had better prognosis than those with early recurrence ( 4 6 ). However, to the best of our knowledge, neither significant factors affecting the survival after recurrence (SAR) for STS patients nor information concerning the prognostic significance of time to local recurrence (TLR) in STS patients have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, tumor local relapse remains one of the major problems in managing STS, and can be defined as early or late recurrence. In breast adenocarcinoma, renal cell carcinoma, and gastric cancer, it was previously reported that patients with late recurrence had better prognosis than those with early recurrence ( 4 6 ). However, to the best of our knowledge, neither significant factors affecting the survival after recurrence (SAR) for STS patients nor information concerning the prognostic significance of time to local recurrence (TLR) in STS patients have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that patients with late recurrence had better survival than those with early recurrence among those with rectal cancer, renal cell carcinoma and gastric cancer. [10][11][12] In cutaneous melanoma, despite several publications investigating the prognostic impact of TTR, the results remain controversial.…”
Section: Discussionmentioning
confidence: 99%
“…However, in patients with cancers such as rectal cancer, renal cell carcinoma or gastric cancer, patients with early TTR were reported to have worse outcomes than those with late TTR. 10 , 11 , 12 On the other hand, survival after recurrence (SAR) is an optimal study endpoint in malignancies with a high prevalence of recurrence, but the prognostic predictors of SAR in cutaneous melanoma have not been well discussed. Such knowledge is, however, valuable for assessing post‐recurrence risk stratification and guiding the appropriate follow‐up schedule.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that early recurrence indicated a dismal prognosis and death risk was twofold higher than those GC patients with late recurrence. 28 These early recurrence-related clinicopathological features might be available for predicting prognosis of GC patients.…”
Section: F I G U R Ementioning
confidence: 99%